2019
DOI: 10.1177/2167696819851433
|View full text |Cite
|
Sign up to set email alerts
|

Parental Discipline in Emerging Adulthood: The Creation and Validation of the Domains of Young Adult Discipline Scale (DYADS)

Abstract: Emerging evidence suggests that parents engage in discipline practices during emerging adulthood, and the use of physical discipline is associated with negative mental health outcomes for emerging adults. However, it appears that no measure of discipline strategies used in emerging adulthood exists. The current study developed the Domains of Young Adult Discipline Scale (DYADS), a measure of parental discipline during emerging adulthood. After item construction, an exploratory factor analysis (EFA) was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This measure is a 24-item scale designed to assess discipline strategies used by parents of emerging adults. Factor analysis in a prior study confirmed a three-factor structure of abuse, approval, and disappointment (Walker & McKinney, 2019). The abuse subscale contains items suggesting power assertion of the parent by use of physical force and restriction of resources (e.g., damages or destroys my property; punches me).…”
Section: Methodsmentioning
confidence: 81%
See 4 more Smart Citations
“…This measure is a 24-item scale designed to assess discipline strategies used by parents of emerging adults. Factor analysis in a prior study confirmed a three-factor structure of abuse, approval, and disappointment (Walker & McKinney, 2019). The abuse subscale contains items suggesting power assertion of the parent by use of physical force and restriction of resources (e.g., damages or destroys my property; punches me).…”
Section: Methodsmentioning
confidence: 81%
“…The disappointment subscale assesses critical and disapproving parenting behaviors (e.g., expresses doubt about my decisions or actions; tells me “I should do better” ). The DYADS demonstrated good convergent validity as it correlated with other measures of parenting style, discipline, and mental health outcomes (Walker & McKinney, 2019). The DYADS demonstrated good internal consistency in the current study (alphas ranging from .89 to .92 across scales in females and males).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations